'A veritable chauvinism of prehistory': nationalist prehistories and the 'British' late Neolithic mythos. Issue 2 (3rd July 2021) - Barclay, Gordon J.; Brophy, Kenneth
ABSTRACT: This article examines the interpretation and public presentation of a particular view of the supposedly 'national' role of monuments in a geographically restricted part of southern England – what we have termed the British late Neolithic mythos: that monuments in the Stonehenge area had a 'national', 'unifying' role for 'Britain' at a time when 'Britain' had a 'unified culture' and was isolated from continental Europe, and that as part of that process, animals for feasting were transported from as far as 'Scotland'. We explore the trajectory of interpretative inflation, 'possible' > 'probable' > 'certain' > 'sensational' through academic and popular accounts, media releases, social media, newspaper articles, TV programmes, Research Excellence Framework impact reports, and the publications of the Arts & Humanities Research Council. We critically examine the evidence claimed to underpin this far-reaching re-interpretation of British prehistory. We examine the extent to which a priori assumptions can shape the interpretation of complex datasets and how unacknowledged nationalist and neo-colonialist thinking underpin its interpretation. We consider the way in which researchers have linked their work with contemporary politics – Brexit, a 'united Britain' isolated from Europe, perhaps to demonstrate 'relevance, 'impact' and 'reach' to funding bodies. We conclude with some suggestions on ways forward including further research, and mitigating strategies.